Organizational Knowledge and Stakeholder Communications: A Substantial Interconnection - Selaković, Marko (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
Within this research (conducted as part of a thesis) the occurence and nature of the interconnection between the application of organizational knowledge preservation and upgrade concepts and efficiency of the stakeholder communications of the companies has been identified. The data related to practices and attitudes are collected by structured interviews with 32 companies: 16 from Western Balkans and 16 from Middle East. Based on the literature review and research findings, the interdependence between the existence of organizational knowledge preservation and upgrade system and the success of the stakeholder communications has been determined.